Direct monitoring of lipid transfer on exposure of citrem nanoparticles to an ethanol solution containing soybean phospholipid by combining synchrotron SAXS with microfluidics - Khaliqi, K.; Ghazal, Aghiad; M. Azmi, Intan Diana; Amenitsch, H.; Mortensen, K.; Salentinig, S.; Yaghmur, Anan (Royal Society of Chemistry, 2017)
Lipid exchange among citrem nanoparticles and an ethanol micellar solution containing soy phosphatidylcholine was investigated in situ by coupling small angle X-ray scattering with a microfluidic device. The produced soy phosphatidylcholine/citrem nanoparticles have great potential in the development of hemocompatible nanocarriers for drug delivery.